DIAGNOSTIC DE L’ELEVAGE DES ANIMAUX DOMESTIQUES AU MANIEMA ET SES INCIDENCES SOCIO-ECONOMICO-SANITAIRES SUR LES ELEVEURS. « CAS DE LA COMMUNE D’ALUNGULI DANS LA PROVINCE DU MANIEMA, RDCongo » - Dr.KABOKABO WA KITUMBA Jean-Jacques,; Ir.MWISSA MUSOKE Venant,; Ir.BULEDI AMURI Lingot, (IJRDO - Journal of Social Science and Humanities Research, 2019)
ALUNGULU’s township is one of the three townships that is in Kindu Town in Maniema province;Additionally, although, this entity be rich in forester potentiality and land, the Diagnosis’s board of domestic animals is dark, on the fact that non of zootechnic is respected, so that many sanitary socioeconomic incidences are recoded and breeder’s lives stagnate and/or drop and so that it’s the principal activity exerted by the population of that region that is also the only interest fount.For reaching explanation, we have used research method supported by direct interview technical, observation, documentary and the statistic technical of percent, have allowed us to treat data. After data analysis, we are arrived to the result to which, the domestic animals breeding in mentioned township is surd, for the animals are raving nourishment is not well balanced, the care is not given and profitability is so absent, so that breeder’s lives is always poorer.